2015
DOI: 10.1002/chem.201500749
|View full text |Cite
|
Sign up to set email alerts
|

Formal Asymmetric Organocatalytic [3+2] Cyclization between Enecarbamates and 3‐Indolylmethanols: Rapid Access to 3‐Aminocyclopenta[b]indoles

Abstract: A highly enantio- and diastereoselective synthesis of 3-aminocyclopenta[b]indoles has been developed through formal [3+2] cycloaddition reaction of enecarbamates and 3-indolylmethanols. This transformation is catalyzed by a chiral phosphoric acid that achieves simultaneous activation of both partners of the cycloaddition. Mechanistic data are also presented that suggest that the reaction occurs through a stepwise pathway.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
12
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 47 publications
(12 citation statements)
references
References 89 publications
0
12
0
Order By: Relevance
“…As part of a program directed toward the stereoselective synthesis of heterocycles, we recently described an efficient enantioselective synthesis of trisubstituted cyclopenta[b]indoles through a chiral‐phosphoric‐acid‐catalyzed (3+2) cycloaddition between alkylideneindoleninium ions generated in situ from indolylarylmethanols and enecarbamates as dienophiles . We also reported that chiral phosphoric acid catalysts were able to efficiently catalyze asymmetric nitroso‐Diels–Alder reactions with 1,3‐diene‐1‐carbamates .…”
Section: Figurementioning
confidence: 99%
“…As part of a program directed toward the stereoselective synthesis of heterocycles, we recently described an efficient enantioselective synthesis of trisubstituted cyclopenta[b]indoles through a chiral‐phosphoric‐acid‐catalyzed (3+2) cycloaddition between alkylideneindoleninium ions generated in situ from indolylarylmethanols and enecarbamates as dienophiles . We also reported that chiral phosphoric acid catalysts were able to efficiently catalyze asymmetric nitroso‐Diels–Alder reactions with 1,3‐diene‐1‐carbamates .…”
Section: Figurementioning
confidence: 99%
“…Gong's work relies on the Brønsted acid catalyzed reaction between 3‐hydroxyoxindoles 121 and enecarbamates 124 (Scheme ) . The entire reaction is orchestrated by phosphoric acid PA 11 , which establishes a network of hydrogen bonds between enecarbamate and vinylogous iminium intermediate . The transformation proceeds smoothly to provide 3,3′‐disubstituted oxindoles 125 with excellent enantioselectivity.…”
Section: Enantioselective Nucleophilic Substitutionsmentioning
confidence: 99%
“…In recent years, 3‐indolylmethanols have emerged as a class of versatile reactants in asymmetric catalysis for the synthesis of enantioenriched indole derivatives 2–4. Especially, chiral phosphoric acid5 (CPA)‐catalyzed transformations involving 3‐indolylmethanols have developed rapidly, which mainly include enantioselective alkylations,3a,b,d,i,j,q–s formal allylation,3n aza‐ene reaction3o and cyclizations 4bi. The significant progress in this research field should largely be ascribed to the unique characteristics of 3‐indolylmethanols.…”
Section: Introductionmentioning
confidence: 99%
“…Among CPA‐catalyzed reactions, the enantioselective [3+2] cyclization of 3‐indolylmethanols with vinylindoles4fh or enecarbamates4i has provided a powerful method for constructing the enantioenriched cyclopenta[ b ]indole framework, which constitutes the core structure of many natural products and pharmacologically important compounds 6. In our previous work, we utilized N‐unprotected 3‐methyl‐2‐vinylindoles4g and 3‐alkyl‐7‐vinylindoles4h as competent reactants in the enantioselective [3+2] cyclization with 3‐indolylmethanols, which benefited from the dual activation mode of CPA [Eqs.…”
Section: Introductionmentioning
confidence: 99%